PENGARUH DESAIN PRODUK DAN ADVERTISING CREATIVITY TERHADAP KEUNGGULAN BERSAING PADA BISNIS BORDIR ONLINE DI TASIKMALAYA: Survei pada konsumen DMK Bordir Tasikmalaya - Raden Anisa Indriani Savitri; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (CV. Ulil Albab Corp, 2022)
Article History: Received: Revised: Accepted: Abstract: This study aims to determine the Simultaneous and Partial Effects between Product Design and Advertising Creativity on Competitive Advantage at the Tasikmalaya Embroidery DMK Company. The research method used is a survey method with a quantitative approach. The sampling technique used non-probability sampling method with a total sample of 100 people. Data collection techniques using online questionnaires. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 24. The results of the study show that Product Design and Advertising Creativity have a significant effect on Competitive Advantage. Partially Product Design has a significant effect on Competitive Advantage. Partially Advertising Creativity has a significant effect on Competitive Advantage.